THEORETICAL ISSUES FINANCIAL AND LEGAL RELATIONSHIP ADMINISTRATIVE AND LIABILITY - Устинова, Ірина Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In article it is conducted the analysis of correlation of financial and administrative responsibility to supporttheoretical basis of identification of financial responsibility as unique kind of jurisdiction responsibility.